Fibromuscular Dysplasia Complicated With Cerebral Stroke in a Child With Congenital Dyserythropoietic Anemia Type II. Issue 8 (November 2016) - Ozcan, Alper; Patiroglu, Turkan; Acer, Hamit; Gumus, Hakan; Senol, Serkan; Karakukcu, Musa; Ozdemir, Mehmet A.; Unal, Ekrem
Abstract : Congenital dyserythropoietic anemia type II belongs to a subtype of bone marrow failure syndrome, which is characterized by monolineage involvement and typical morphologic abnormalities in erythroid precursor cells resulting in different degrees of hyporegenerative anemia. Moreover, reticulocytosis, which is not corresponding to the degree of anemia, with jaundice and splenomegaly are major diagnostic criteria. Causative gene is located at SEC23B. Although stroke among children is rare, it can cause significant morbidity and mortality. Herein we present a 3-year-old male with congenital dyserythropoietic anemia type II who presented with stroke-like symptoms, and was diagnosed with fibromuscular dysplasia.